Pembelajaran Aqidah Akhlaq Berbasis Word Square: Strategi Game-Based Learning dalam Penguatan Minat dan Capaian Belajar Siswa - Miftahrudin; Moh. Bisri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study aims to analyze the effectiveness of the Word Square method in improving learning outcomes and student engagement in Islamic Religious Education (PAI) learning. The Word Square method is understood as a game-based learning strategy that positions students as active subjects in the learning process (student-centered learning), while also promoting the strengthening of concept comprehension, concentration, and learning motivation. This study uses a descriptive qualitative approach through literature review and conceptual analysis of various scientific sources relevant to PAI learning and innovative active learning methods. The study results indicate that the Word Square method has significant pedagogical potential in creating PAI learning that is interactive, enjoyable, and meaningful. From a managerial-pedagogical perspective, this method supports the development of students' cognitive, affective, and social skills through game-based concept search activities, collaboration, and reflection on Islamic values. The novelty of this study lies in emphasizing the position of Word Square not only as an evaluative technique but also as an educational game-based PAI learning model that aligns with the 21st-century learning paradigm. The conceptual implications of this study affirm that integrating the Word Square method in PAI learning can strengthen student-centered and game-based learning approaches to improve the quality of the learning process and outcomes. Therefore, PAI teachers need to develop adaptive and creative learning designs by utilizing game-based methods as part of pedagogical innovation focused on active engagement and character building of students.